2012
DOI: 10.1186/1746-6148-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes involved in hepatic carnitine synthesis and uptake in dairy cows in the transition period and at different stages of lactation

Abstract: BackgroundIn rodents and pigs, it has shown that carnitine synthesis and uptake of carnitine into cells are regulated by peroxisome proliferator-activated receptor α (PPARA), a transcription factor which is physiologically activated during fasting or energy deprivation. Dairy cows are typically in a negative energy balance during early lactation. We investigated the hypothesis that genes of carnitine synthesis and uptake in dairy cows are enhanced during early lactation.ResultsmRNA abundances of PPARA and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 42 publications
9
69
5
Order By: Relevance
“…Mean expression of SLC27A1 was highest in wk 1 p.p. in the present study along with highest plasma NEFA and liver TG concentration, in agreement with Schlegel et al (2012), and interestingly elevated for feed-restricted cows compared with control cows. To our knowledge, this paper shows distinct results on expression of SLC27A1 in the bovine liver during feed restriction in mid lactation for the first time.…”
Section: Gene Expression Of Parameters and Enzymes Related To Lipid Msupporting
confidence: 76%
See 1 more Smart Citation
“…Mean expression of SLC27A1 was highest in wk 1 p.p. in the present study along with highest plasma NEFA and liver TG concentration, in agreement with Schlegel et al (2012), and interestingly elevated for feed-restricted cows compared with control cows. To our knowledge, this paper shows distinct results on expression of SLC27A1 in the bovine liver during feed restriction in mid lactation for the first time.…”
Section: Gene Expression Of Parameters and Enzymes Related To Lipid Msupporting
confidence: 76%
“…An aliquot (~40 mg) of the liver tissue was frozen immediately at −20°C until determination of TG content. Liver TG content was measured after extraction according to Schlegel et al (2012). In brief, lipids from biopsy tissue were extracted with a mixture of n-hexane and isopropanol (3:2, vol/vol).…”
Section: Blood Collection and Analyses Of Metabolitesmentioning
confidence: 99%
“…The key genes that are involved in regulating energy metabolism in multiple tissues include PPRA, PCK1, PCK, ACACA, FASN, FBP2, FABP3, PPARGC1A, ACSL1, PPARGC1A, AGPAT6, PCCA, LPIN1, ACO, CPT-I, CPT-II and ACSL [4,15,27,94,131,163]. These genes are involved in fatty acid uptake (mainly in the liver and mammary gland), mitochondrial and peroxisomal fatty acid oxidation, ketone body metabolism (ketogenesis) and cholesterol metabolism (in liver) early in lactation in dairy cattle [135] and are discussed in the following tissue-specific sections in more detail.…”
Section: Genes and Key Pathways Affecting Multiple Tissuesmentioning
confidence: 99%
“…1), and TAG in liver [129,135]. Several genes and pathways in multiple tissues are involved in regulating these metabolites in lactating dairy cows [14,15,23,53,90,98,135]. A gene-based mapping and pathway analysis indicated that three pathways (steroid hormone biosynthesis, ether lipid metabolism and glycerophospholipid metabolism) jointly affect the concentrations of NEFA, BHBA and glucose in cows during the transition period [53].…”
Section: Genes and Key Pathways Affecting Multiple Tissuesmentioning
confidence: 99%
See 1 more Smart Citation